Recent Trends In The Study Of Digital And Contemporary Arts An Analytical Study In The Light Of The Criteria Of Beauty And Ugliness - Dr. Tahani Mohammad Nasser AL-Arifi (Elementary Education Online, 2023)
This study observes transitions from semi democratic art to expression of none objective, and use of technology that brought an infinite sphere of art in Pakistan. Popular art movement assimilates truck art, cinema hoardings and wedding motifs in the cities and urban areas. Artists explored freely electronic media, digital art forms, photography and film to communicate expressions in individual ways. Kind of depiction engaged in concept oriented artworks due to all prescribed reasons is most remarkable. Artists freely combining modern ethnicity with tradition, continued to expand the potential discovered by preceding generation and kept on insert additional dimensions. Artists rejected conventional artistic media. For the reason, artistic development inclines into intellectual investigation and manifestation despite beauty and aesthetic pleasure. It is believed that distinctiveness of art works is in idea and contemporary artist are remarkably contributing to this theory.